CONVENTION REPORT. (The Accounting Review, 1933)
This article presents information on the 17th annual convention of American Association of University Instructors in Accounting which was held in Cincinnati, Ohio from December 28-29, 1932. Various topics discussed at the convention were recent Developments in accounting methods, problems of accounting teaching, accounting and law and problems of accounting research. The article also presents a list of professors who had read papers on these topics during the convention. The annual dinner was held on December 28, at 7:00 p.m. After introductions in which each member in turn arose, announced his name and his connection, professor F.W. Woodbridge announced the name of the winner of the scroll awarded by Beta Alpha Psi, the national accounting fraternity in the U.S., for the most notable contribution to accounting literature during the year ended April 30, 1932. The scroll was awarded to A.P. Richardson, editor of "Journal of Accountancy," for his book "The Ethics of a Profession." Following the announcement of the award, J.L. Carey, secretary of the American Institute of Accountants was introduced and he spoke briefly.